Hepatic Tuberculosis of Pseudotumor Form - Sabbah Meriam; Bibani Norsaf; Trad Dorra; Ouakaa Asma; Elloumi Hela; Gargouri Dalila; Lahmar Ahlem; Kharrat Jamel (Journal of Spleen And Liver Research, 2018)
Tuberculosis involving the liver in the absence of active pulmonary tuberculosis is very rare. The inflammatory pseudotumoral form is an entity difficult to diagnose. We report a case of an inflammatory pseudotumor of the liver due to tuberculosis, who didn’t underwent hepatectomy because of the size of the tumor. The diagnosis of tuberculosis was made on biopsy and Polymerase Chain Reaction (PCR).
Keywords: Hepatic Tuberculosis